Determining the Difference between the Chronological and Biological Age of Athletes Diagnosed with Trigeminal Neuralgia - MIOČIĆ, Josip; KOMŠO, Milica; JERAK, Tonći (Studia Universitatis Babeș-Bolyai. Educatio artis gymnasticae, 2025)
Trigeminal neuralgia induces severe, often intolerable pain in patients—athletes, in this context—that is frequently resistant to currently available therapeutic options. The International Association for the Study of Pain (IASP) defines trigeminal neuralgia as a sudden, typically unilateral, intense, brief, stabbing, and recurring episode of pain in the distribution of one or more branches of the trigeminal nerve. The condition may be caused by vascular compression of the trigeminal nerve, tumor-related processes, or multiple sclerosis. Compression of the nerve itself leads to demyelination, which results in abnormal depolarization and the generation of ectopic impulses. Triggers for pain may include heat, cold, eating, breathing, tooth brushing, shaving, or incidental contact. Once diagnosed by a specialist, magnetic resonance imaging (MRI) is required to confirm or exclude multiple sclerosis. Tumorous processes may also secondarily lead to trigeminal neuralgia. The first-line pharmacological treatment remains carbamazepine. If pharmacotherapy proves ineffective, more invasive interventions such as microvascular decompression, stereotactic radiosurgery (Gamma Knife), percutaneous balloon microcompression, glycerol rhizolysis, and radiofrequency (RF) ablation may be considered. This study is unique in that its sample comprises athletes diagnosed with trigeminal neuralgia. The primary objective is to examine potential differences between their chronological and biological age by analyzing their metabolic age. The findings aim to support and potentially initiate a novel paradigm or theoretical framework concerning the remodeling of biological aging in athletes suffering from trigeminal neuralgia, particularly in the context of optimizing training processes. Article history: Received 2025 July 18; Revised 2025 October 08; Accepted 2025 October 23;Available online 2025 November 20; Available print 2025 November 30